Beyond human touch: how AI is reshaping the publishing industry - Abu Bakar, Muhammad Nabihan; Hassan @ Asan, Amirah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Artificial Intelligence (AI) encompasses advanced technologies that replicate human intelligence, including decision-making and learning from experience. In the publishing industry, AI is increasingly integrated across departments such as editorial, design, marketing, and production. These technologies enhance efficiency, accuracy, and overall workflow. AI tools like GPT models aid in content creation by generating articles and reports, reducing time and manual effort. They also support design, editing, and personalised marketing strategies. This transformation leads to improved quality and user engagement. Overall, AI plays a vital role in modernising publishing practices.